EVALUACIÓN DE Lactuca sativa Y Selenastrum capricornutum COMO INDICADORES DE TOXICIDAD EN AGUAS - P. Bohórquez-Echeverry; C. Campos-Pinilla (Universitas Scientiarum)
The use of Selenastrum capricornutum in acute toxicity assessment is a potentially useful toolin water monitoring. The main objective of this study was to compare the sensitivity of S.capricornutum with the extensively used Lactuca sativa bioassay in water and to select the bestindicator. For this purpose, inhibition or stimulation effects of algae cell growth and seed growthwere determined as end points. Sensitivity of both organisms was determined with Zn (II) asreference toxicant to homologate the results between S. capricornutum and L. sativa. However,when Selenastrum was exposed to Zn (II) there was a strong variation in results. Therefore, Cr(VI) was used as a reference toxicant. The CE50-120h value for Zn (II) for L. sativa was 24.48 mg/Land the CE50-96h value for Cr (VI) for S. capricornutum was 0.29 mg/L. Two environmentalsamples were collected from the Bogotá River and other from the Salitre wastewater treatmentplant, to evaluate sensitivity of indicators. Results showed similar responses on both organisms,possibly due to the organic matter concentration in evaluated samples.